THE EFFECT OF USE OF LIQUID ORGANIC FERTILIZER OF TURI PUTIH ( Sesbania grandiflora) LEAVES WITH DIFFERENT DOSES OF POPULATION DENSITY AND GROWTH RATE OF Chlorella sp. - Nuraini Nuaraini; Sukendi Sukendi; Leodewik Murdani Simanjuntak (Berkala Perikanan Terubuk, 2020)
This research was conducted in December 2019 and January 2020 at the Fish Breeding and Breeding Laboratory of the Faculty of Fisheries and Maritime Affairs, Riau University. The purpose of this study was to determine the effect and optimal dosage of organic fertilizer fermented from white turi leaves (Sesbania grandiflora) on the culture of Chlorella sp. The design of this study was an experimental model using a completely randomized design factorial pattern (CRD) of 1 factor, 4 levels of treatment and 3 replications. The treatment level used was P0 (control, Walne 2ml / L). P2 (white turi leaf fertilizer dose 2 ml / L), P3 (3 ml / L), and P4 (4 ml / L). Cultivation was carried out for 10 days, using Turi Putih and Walne Leaf Fertilizers. The results showed that administration of different doses of white turi leaf fertilizer affected population density and specific growth rates. Application of white turi leaf fertilizer with a dose of 4 ml / L gives the best results with a cell density of 573.33 x 104 cells / ml, and a specific growth rate of 1.8651 / day, and the highest peak density occurs on day 7. Results of quality measurements water during the study obtained a temperature of 29-33 oC, pH 7.8- 8.5, and DO 8.0-8.5.